The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.14710/kapal.v18i3.41010
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis into the Resistance of Trimaran with Longitudinal Sidehull Adjustments

Abstract: There has recently been a surge in demand for multi-hull vessels for military and commercial purposes. The need for multi-hull ships increase from the necessity to balance speed and cargo requirements. Among others, the trimaran is one such hull type. The current study performs a CFD resistance analysis for trimaran as a parameter range of feasible hull forms based on the NPL systematic series. The resistance of trimaran hull shapes are calculated using CFXTM, a commercial CFD code that belongs to ANSYS. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the numerical method has the same phenomenon as the experiment: the ship has self-righting in all condition load cases. Numerical methods such as CFD have become famous for marine use, such as fast ship design [3,4] and ship performance [5,6]. Another CFD scheme such as mesh-free CFD, i.e., smoothed particle hydrodynamics (SPH) that is suitable for marine engineering cases such as water wave propagation [7,8] and sloshing in LNG cases [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the numerical method has the same phenomenon as the experiment: the ship has self-righting in all condition load cases. Numerical methods such as CFD have become famous for marine use, such as fast ship design [3,4] and ship performance [5,6]. Another CFD scheme such as mesh-free CFD, i.e., smoothed particle hydrodynamics (SPH) that is suitable for marine engineering cases such as water wave propagation [7,8] and sloshing in LNG cases [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…As a form of floating media, the ship will experience movement caused by internal factors due to the ship itself or external factors such as sea waves. High sea waves accompanied by extreme and rapidly changing weather conditions can cause discomfort and may further threaten the safety of the soul at sea [5]. Therefore, in designing a ship, one aspect that needs to be considered is the safety and comfort of the crew on board.…”
Section: Introductionmentioning
confidence: 99%